The Digital Divide : How Madrasah Uses Technology to Improve Brand Image - Ainul Yakin; Mohammad Dendy Musthofa; Hendi Kurniyawan; Hasan Baharun; Hefniy Hefniy (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
This study aims to explore the use of digital technology by Madrasah Tsanawiyah Darul Musthofa in improving the institution's brand image. Using a qualitative approach with a case study method, data was collected through semi-structured interviews, participant observation, and document analysis. The results of the study show that the strategic use of social media such as YouTube, TikTok and WhatsApp has succeeded in increasing public trust in the quality of madrasah education. Digitization of learning also strengthens engagement between students, teachers, and parents, although limited infrastructure and technological training remain significant challenges. The implication of this research is the need for a planned strategy and policy support to ensure equitable adoption of technology, especially in rural areas. This study contributes by understanding the synergy between digital technology and brand image enhancement strategies in the context of Islamic education, offering strategic guidance for other madrasahs to compete in the digital era.